DM management in HIV patients: the adoption of population health management to transform the chronic management of HIV. (8th September 2022) - Pacileo, Guglielmo; Morando, Verdiana; Banks, Helen; Ferrara, Lucia; Cattelan, Annamaria; Luzzati, Roberto; Manfrin, Vinicio; Tozzi, Valeria Domenica
Abstract: Background: The success of antiretroviral therapies has made human immunodeficiency virus (HIV) a chronic disease, changing the care scenario dramatically. This study aimed to measure adherence to diabetes mellitus standards of care provided for people living with HIV (PLWH). Diabetes represents a paradigmatic case for tackling chronic care management in this target group. Methods: This retrospective observational study was performed on administrative health data retrieved from 2014 to 2016, with a validated algorithm to identify patients with HIV using: (i) hospital discharge records (ICD9-CM codes); (ii) drug dispensing records (with ATC codes); and (iii) disease-specific exemptions from co-payments for healthcare services. HIV-related treatments, comorbidities and health service utilization were measured, as was adherence to clinical guidelines-recommended standards of care for diabetes. Results: A population of 738 cases were identified in two Local Health Authorities in Italy, representing a prevalence of 0.14% of the general population, in line with the expected prevalence. Thirty-one cases of HIV patients diagnosed with diabetes were identified, a prevalence ratio of 4.2% compared to the 8% in the overall population. Adherence to diabetes standards of care tested within the same population was low, with the exception of those tests commonly administered for standard HIV follow-up care. Conclusions: The use of administrative data, combined with a Population Health Management approach represents a powerful tool for evaluating system capacity to manage HIV comorbidities. Study findings prove that it is time to design new care models for PLWH, affected by one or more chronic conditions, both to prevent their onset and to manage their comorbidities.